Selective induction of apoptosis in MCF7 cancer-cell by targeted liposomes functionalised with mannose-6-phosphate. (16th March 2018) - Minnelli, Cristina; Cianfruglia, Laura; Laudadio, Emiliano; Galeazzi, Roberta; Pisani, Michela; Crucianelli, Emanuela; Bizzaro, Davide; Armeni, Tatiana; Mobbili, Giovanna
Abstract: Liposomes are versatile platforms to carry anticancer drugs in targeted drug delivery; they can be surface modified by different strategies and, when coupled with targeting ligands, are able to increase cellular internalisation and organelle-specific drug delivery. An interesting strategy of antitumoral therapy could involve the use of lysosomotropic ligand-targeted liposomes loaded with molecules, which can induce lysosomal membrane permeabilization (LMP), leakage of cathepsins into the cytoplasm and subsequent apoptosis. We have previously demonstrated the ability of liposomes functionalised with a mannose-6-phosphate to reach lysosomes; in this research we compare the behaviour of M6P-modified and non-functionalised liposomes in MCF7 tumour cell and in HDF normal cells. With this aim, we first demonstrated by Western blotting the overexpression of mannose-6-phosphate/insulin-like growth factor (M6P/IGF-II) receptor in MCF7. Then, we prepared calcein-loaded liposomes and we revealed the increased uptake of M6P-functionalised liposomes in MCF7 cells respect to HDF cells by flow cytometry analysis. Finally, we loaded functionalised and not functionalised liposomes with N -hexanoyl-d - erythro -sphingosine (C6Cer), able to initiate LMP-induced apoptosis; after having studied the stability of both vesicles in the presence of serum by Dynamic Light Scattering and Spectrophotometric turbidity measurements, we showed that ceramide-loaded M6P-liposomes significantly increased apoptosis in MCF7 with respect to HDF cells.